Answer :

shreethini1

Answer:

-89

The difference between the sequence is - 4

So for each term you add (-4) to get the next term

To find the 22nd term, you can make an equation using this sequence. So you find the 0th term, which is the term before the one which is given. To find that you do - 5 - (-4)=-1

So 0th term is - 1, therefore - 1 - 4n is the equation

Check:

-1-4(1)=-5(first term)

-1-4(2)=-9(second term)

Therefore, to find the 22nd term

-1-4(22) = - 1-88 = - 89

Other Questions